2020
DOI: 10.1101/2020.09.01.277947
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calcium-dependent protein acyltransferase DHHC21 controls activation of CD4+T cells

Abstract: Despite the recognized significance of reversible protein lipidation (S-acylation) for T cell receptor signal transduction, the enzymatic control of this post-translational modification in T cells remains poorly understood. Here, we demonstrate that DHHC21, a member of the DHHC family of mammalian protein acyltransferases, mediates agonist-induced S-acylation of proximal T cell signaling proteins. Using Zdhhc21dep mice expressing a functionally deficient version of DHHC21, we show that DHHC21 is a calcium/calm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It is also worth noting that acyl-group exchange methods provide snapshot-like profiles of S-acylated proteins at a given time point. Our group and others used these methods over a time course to evaluate the dynamic S-acylation ( Chen et al, 2020 ; Shayahati et al, 2020 ).…”
Section: Methods Of Detecting S-acylationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth noting that acyl-group exchange methods provide snapshot-like profiles of S-acylated proteins at a given time point. Our group and others used these methods over a time course to evaluate the dynamic S-acylation ( Chen et al, 2020 ; Shayahati et al, 2020 ).…”
Section: Methods Of Detecting S-acylationmentioning
confidence: 99%
“…We also found that the rapid palmitoylation of Lck following Fas stimulation is dependent on intracellular calcium levels. This is likely mediated by a calcium/calmodulin binding site in the C-terminal tail of DHHC21 ( Shayahati et al, 2020 ). Interestingly, we found that though APT1 deacylates Lck under resting conditions, it does not affect stimulus-dependent deacylation following Fas stimulation.…”
Section: Dynamic S-acylation/deacylationmentioning
confidence: 99%
“…Recently, it has been found that S-acylation is required for the proper function of the immune system. For example, several key signaling T cell receptor proteins were identified as S-acylated, and this modification has been found to be critical for proper protein localization, function, and propagation of T cell receptor signaling in response to antigenic stimulation ( Tewari et al, 2021 ; Fan et al, 2020 ; Shayahati et al, 2021 ). Although a lot of progress has been made in the S-acylation field in the last decade, the full extent of S-acylation in T cells is still not fully understood or appreciated.…”
Section: Introductionmentioning
confidence: 99%